Tafsir Resmi Versi Pemerintah di Indonesia - Siti Pajriah; Sahlan Muhammad Faqih (UIN Sunan Gunung Djati Bandung, 2021)
In 1965 a translation of the Holy Koran of the Ministry of Religion was printed, consisting of three volumes. During the New Order government, 1972, a team of experts on the interpretation of the Koran was formed. Three years later, in 1975, published for the first time a volume of one-volume tafsir of the first three chapters of the Koran, 1980 this tafsir work was complete up to thirty juz. Also, the government also enriches the interpretation and translation of the Koran using local dialects and the treasury of the Indonesian Koran. For example, the translation and interpretation of the Sundanese Koran published by the provincial government and the West Java regional office of the Ministry of Religion. Besides, the Indonesian Ministry of Religion's Research and Development Center for Literature has published a translation of the Koran in Sundanese, along with the publication of a translated Koran using 15 other local languages. The formulation of the government's interpretation underwent changes that coincided with the transition of power from the New Order to the reformation. The difference is evident in the approach of its interpretation which has shifted from al-tahlîli (descriptive-analytical) with an hidâ'i (guidance) style to a method maudû'i (thematic) with an 'ilmî (scientific) style.